A pH-Sensitive Function and Phenotype: Evidence that EutH Facilitates Diffusion of Uncharged Ethanolamine in Salmonella enterica - Penrod, Joseph T. (American Society for Microbiology, 2004)
The eutH gene is part of an operon that allows Salmonella enterica to use ethanolamine as a sole source of nitrogen, carbon, and energy. Although the sequence of EutH suggests a role in transport, eutH mutants use ethanolamine normally under standard conditions (pH 7.0). These mutants fail to use ethanolamine at a low pH. Evidence is presented that protonated ethanolamine (Eth(0)) does not enter cells, while uncharged ethanolamine (Eth(0)) diffuses freely across the membrane. The external concentration of Eth(0) varies with the pH (pK = 9.5). At pH 7.0, the standard ethanolamine concentration (41 mM) provides enough Eth(0) for an influx rate that can support growth with or without EutH. When a lowered pH and/or ethanolamine concentration reduced the Eth(0) concentration below 25 μM, EutH was needed to facilitate diffusion. EutH(+) cells grew normally at Eth(0) concentrations above 3 μM, close to the Km (9 μM) of the first degradative enzyme, ethanolamine ammonia lyase. It is suggested that EutH facilitates diffusion of Eth(0). As predicted for a transporter, EutH contributed to the toxicity of ethanolamine seen under some conditions; furthermore, fusion of EutH to fluorescent Yfp protein provided evidence that EutH is a membrane protein.